2010
DOI: 10.1002/etc.146
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and biotransformation of uncoated and coated nickel hydroxide nanoparticles on mesquite plants

Abstract: Nanomaterials are of particular interest in environmental chemistry due to their unknown toxicity to living organisms. Reports indicate that nanoparticles (NPs) affect seed germination, but the uptake and biotransformation of metal nanoparticles is not well understood. The present study investigated the toxicity and biotransformation of Ni(OH)2 NPs by mesquite plants (Prosopis sp.). Three sets of plants were treated for four weeks with 0.01, 0.05, or 0.10 g of either uncoated or sodium citrate coated NPs befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 32 publications
4
63
0
Order By: Relevance
“…However, Barrena et al (2009) reported low or no toxicity after exposing cucumber and lettuce to 10 nm Au and 7 nm Fe 3 O 4 MNMs. Parsons et al (2010) reported that exposure mesquite plants to Ni(OH) 2 MNMs had no effect on biomass production, shoot elongation, or root elongation. Navarro et al (2012) found that Arabidopsis plants produced reduced glutathione relative to oxidized glutathione after exposure to CdSe/ZnS quantum dots, indicating that the MNMs induced oxidative stress in the plants.…”
Section: Ceomentioning
confidence: 97%
“…However, Barrena et al (2009) reported low or no toxicity after exposing cucumber and lettuce to 10 nm Au and 7 nm Fe 3 O 4 MNMs. Parsons et al (2010) reported that exposure mesquite plants to Ni(OH) 2 MNMs had no effect on biomass production, shoot elongation, or root elongation. Navarro et al (2012) found that Arabidopsis plants produced reduced glutathione relative to oxidized glutathione after exposure to CdSe/ZnS quantum dots, indicating that the MNMs induced oxidative stress in the plants.…”
Section: Ceomentioning
confidence: 97%
“…It is clear from our imaging data, both by autoradiography and PET/CT (Figures 2 and 3) that the 64 Cu]-NPs (11, 20 nm) had a size that appeared smaller than those administered; suggesting that the plant may filter larger NPs and has a size-threshold for uptake ( Figure 6E, F), which may also explain the clogging phenomenon. 27,28,48 In summary, the combined analysis of the imaging by autoradiography and PET/CT (Figures 2 and 3) and TEM ( Figure 6) 45 The amount found in the leaves varied from 400 to 803 μg/g of mesquite with most the NPs remaining in the roots ranging from 12 835 to 38 183 μg/g. 45 Another study using small CeO 2 -NPs (7 nm) exhibited NP accumulation ranging from 300 to 6000 μg/g of plant (corn, soy bean, cucumber, tomato, and alfalfa) and indicated that NP accumulation was plant species dependent.…”
Section: ■ Discussionmentioning
confidence: 93%
“…The extensive range of NP accumulation reported in plants suggests that NP-uptake is dependent on several parameters: (1) quantity of NP administered per plant, (2) plant species, (3) NP-size, (4) NP-composition, and (5) duration of exposure. 1,12,[14][15][16][17][18]45 Further complicating the understanding of NP transport and accumulation in plants are the studies that have observed NP-uptake due to dissolution. 14,17−19,33−35 Collectively the variations of parameters in every study on NP transport in plants have made direct comparison and accurate conclusions challenging.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Homogeneous dispersions can be achieved by amendment with external surfactants or through the use of surface functionalized ENMs. For example, multi-wall carbon nanotubes (MWCNTs) and C 70 fullerene were stabilized in natural organic matter (NOM, including humic acid) and gum Arabic solutions in the media (Lin et al, 2009;Larue et al, 2012b); metal-based ENMs such as Fe 3 O 4 , Au, Ag, and Ni(OH) 2 were coated with citrate, tannate, or polyvinylpyrrolidone (PVP) (Parsons et al, 2010;Wang H. et al, 2011;Judy et al, 2012a;Lee et al, 2012). There are also reports using agar or semi-solid media such as Murashige and Skoog (MS) medium that may be amended with ENMs prior to solidification (Lee et al, 2008;Miralles et al, 2012b;Yang et al, 2012;Yan et al, 2013).…”
Section: Laboratory Designed Exposure Conditionsmentioning
confidence: 99%
“…In addition, quantum effects become significant with size reduction, subsequently changing particle optical, electrical, and magnetic behaviors. However, great variation exists among different ENMs, including size, shape, physical conformation, specific surface area, surface charge, and the presence of coatings/functionality (Hassellov et al, 2008;Parsons et al, 2010;Pan and Xing, 2012). From the perspective of nanobiological interactions, the most attractive ENMs traits include a high degree of surface reactivity and a size-dependent ability to cross biological membranes.…”
Section: Introductionmentioning
confidence: 99%